Analysis of integral field spectroscopy observations of the planetary nebula Hen 2-108 and its central star. Issue 1 (7th April 2023) - Miranda Marques, Bárbara L; Monteiro, Hektor; Aleman, Isabel; Akras, Stavros; Todt, Helge; Corradi, Romano L M
ABSTRACT: The study of planetary nebulae provides important constraints for many aspects of stellar and Galactic evolution. Hen 2-108 is a poorly known planetary nebula with a slight elliptical morphology and a peculiar central star (CS), which has defied classification. In this work, we present the first detailed integral field spectroscopic study of the planetary nebula Hen 2-108 and its CS. We provide spatially resolved flux maps for important emission lines, as well as diagnostic maps of extinction and electronic density and temperature. Physical conditions and chemical abundances were also calculated from the integrated spectrum. The analysis was also performed with the code satellite that uses a distinct strategy to evaluate physical and chemical properties. Both satellite and traditional procedure give consistent results, showing some variation in physical and chemical properties. We detect and measure a number of faint heavy element recombination lines from which we find a significant abundance discrepancy factor for O/H, and possibly for N/H. Pseudo-3D photoionization models were used to assist in the interpretation with results supporting the low-ionization nature of this nebula, indicating a CS with T eff = 40 kK and a shell structure. The spectrum of the CS has been analysed with a detailed model for expanding atmospheres to infer stellar parameters, finding that it is a [Of/WN8] type with T * = 41.5 kK, making it a new addition to a small set (∼20) of rare objects.